ANALISIS KELAYAKAN USAHA ALUMINIUM DAN KACA DITINJAU DARI ASPEK PRODUKSI DAN PEMASARAN (STUDI KASUS TOKO M.A KACA DAN ALUMINIUM PADANG PANJANG) - Lucky Mahesa Yahya; Maulidini Adha; Mutiara Novelly Asril; Dedi Firmansyah (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2023)
Aluminum and glass are experiencing rapid development. The rapid development of the aluminum and glass industry is caused by several factors such as materials from wood which are limited and quite difficult to find, increasing residential and business development, and increasing public demand for goods made of aluminum. Currently, many Aluminum and Glass MSMEs have sprung up, so researchers are interested in conducting research entitled